Crucial Contextual Theological Analysis Ma’nene’ Ritual In The View Bevans’ Anthropological Model - Benny Agustinus Triangga Prayitno; Hosianna Hosea (LPPM Universitas PGRI Sumatera Barat, 2024)
The discussion of Christian faith in the context of culture is a very crucial and interesting matter to be adjusted to the life of the church today. This adjustment is specifically seen in the context of the life of the Toraja people who are predominantly Christian, but are very strong in every cultural issue that is considered a fundamental thing in the life of the Toraja. The writing of this scientific work aims to bring readers to understand how the Ma'Nene' traditional ritual is based on the context of Torajan life seen in one of Bevans' models, namely the